2005
DOI: 10.1007/s10143-005-0411-8
|View full text |Cite
|
Sign up to set email alerts
|

VEGF plasma levels in nonruptured intracranial aneurysms

Abstract: Aneurysm growth appears to be associated with an increased risk of rupture. Therefore, it may be of interest to identify mechanisms contributing to aneurysm growth. Angiogenic factors, particularly vascular endothelial growth factor (VEGF), appear to play an important role in the pathogenesis and growth of cerebrovascular malformations. We aimed to study systemic VEGF levels as a potential systemic marker in patients with non-ruptured intracranial aneurysms compared with healthy controls. Mean VEGF plasma conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…12 A recent study reported a significant increase in circulating VEGF levels in AVM patients compared to healthy controls. 40 Increased expression of circulating VEGF has also been associated with other cerebrovascular disorders including intracranial aneurysms, 41 dural arteriovenous fistulas, 21 and vasospasm after subarachnoid hemorrhage. 5 VEGF expression is regulated by numerous factors, most significantly hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study reported a significant increase in circulating VEGF levels in AVM patients compared to healthy controls. 40 Increased expression of circulating VEGF has also been associated with other cerebrovascular disorders including intracranial aneurysms, 41 dural arteriovenous fistulas, 21 and vasospasm after subarachnoid hemorrhage. 5 VEGF expression is regulated by numerous factors, most significantly hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal degeneration of intracranial arteries is a complex biological response reflecting the interplay of numerous inherited and acquired factors. 26) VEGF was expressed on the walls of all cerebral aneurysms analyzed. 28) In contrast, no VEGF expression was found on normal vessels.…”
Section: Discussionmentioning
confidence: 92%
“…Its plasma level is also elevated (eg, in patients with intracranial aneurysms). 12 These aneurysms have a significantly higher detection rate in patients with polycystic kidney diseases, which in turn are associated with Caroli disease. Interestingly, cholangiocytes derived from livers affected with Caroli disease have been shown to overexpress VEGF and its receptors.…”
Section: Figurementioning
confidence: 99%